Reproductive neuroendocrine defects programmed by prenatal testosterone treatment between gestational days 60–90 are amplified by postnatal obesity in sheep - Gurule, S. C.; Sustaita-Monroe, J. F.; King, L. N.; Landers, R. S.; Garza, V.; West, S. M.; Bynum, S. E.; Perry, L.; Padmanabhan, V.; Cardoso, R. C. (Frontiers in Physiology, 2024)
Polycystic ovary syndrome (PCOS) is the leading cause of anovulatory infertility in women of reproductive age and obesity can increase the severity and development of the PCOS phenotype. Prenatal testosterone (T) treatment between gestational days 30 to 90 advanced puberty and disrupted the reproductive and metabolic phenotype in female sheep, recapitulating attributes of women with PCOS, with postnatal obesity amplifying its severity. On the other hand, prenatal T treatment from gestational days 60-90 led to a much milder phenotype. We hypothesized that reproductive neuroendocrine defects programmed by prenatal T treatment between gestational days 60-90 are amplified by postnatal obesity in sheep. Suffolk ewes received T propionate (T; 100 mg) or corn oil (C; vehicle) twice weekly from gestational days 60-90. At 5 mo of age, T lambs were assigned to either a maintenance (100% of NRC requirements) or overfed diet (130% NRC) and C lambs were fed the maintenance diet. Timing of puberty (n=15/group) determined by twice weekly measurement of progesterone concentrations, estradiol positive feedback responsiveness (n=8/group) determined by assessment of LH secretion in response to exogenous estradiol, periovulatory LH dynamics during the second breeding season (n=8/group) following synchronization with two injections of PGF2α, and progesterone negative feedback (n=8/group) determined by characterizing LH pulses during the mid-luteal phase were compared between C, T-maintenance and T-overfed groups. Findings indicate that postnatal obesity: 1) exacerbated reproductive defects and further deteriorated reproductive cyclicity during the second breeding season (adulthood); 2) did not amplify the impairment in estradiol positive feedback in delaying the timing and amplitude of the LH surge although it reduced the total amount of LH secreted during the preovulatory LH surge; and 3) amplified the reduced responsiveness to progesterone negative feedback manifested as an increase in LH pulse amplitude and peak. These observations in addition to supporting our previous findings that prenatal T treatment results in reproductive neuroendocrine dysfunction and periovulatory disruptions provide evidence that these neuroendocrine defects programmed between gestational days 60-90 are amplified by postnatal obesity in female sheep.